Development of a New Patient-reported Outcome Measure for Ear Conditions: The EAR-Q. Issue 8 (August 2018) - Klassen, Anne F.; Longmire, Natasha M.; Bulstrode, Neil W.; Fisher, David M.; Kasrai, Leila; O'Hara, Justine; Panchapakesan, Vivek; Pusic, Andrea L.; Stewart, Ken; Tsangaris, Elena; Ziolkowski, Natalia; Wong Riff, Karen W. Y.
Abstract : Background: Patient-reported outcome measures are widely used to improve health services and patient outcomes. The aim of our study was to describe the development of 2 ear-specific scales designed to measure outcomes important to children and young adults with ear conditions, such as microtia and prominent ears. Methods: We used an interpretive description qualitative approach. Semi-structured qualitative and cognitive interviews were performed with participants with any type of ear condition recruited from plastic surgery clinics in Canada, Australia, United States, and United Kingdom. Participants were interviewed to elicit new concepts. Interviews were audio-recorded, transcribed, and coded using the constant comparison approach. Experts in ear reconstruction were invited to provide input via an online Research Electronic Data Capture survey. Results: Participants included 25 patients aged 8–21 years with prominent ears (n = 9), microtia (n = 14), or another condition that affected ear appearance (n = 2). Analysis of participant qualitative data, followed by cognitive interviews and expert input, led to the development and refinement of an 18-item ear appearance scale (eg, size, shape, look up close, look in photographs) and a 12-item adverse effects scale (eg, itchy, painful, numb). Conclusions: The EAR-Q in currently being field-tested internationally. Once finalized, we anticipate the EAR-Q will be used in clinical practice and research to understand the patient's perspective of outcomes following ear surgery.